2003
DOI: 10.1210/jc.2002-021499
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Intolerance, Insulin Resistance, and Hyperandrogenemia in First Degree Relatives of Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is associated with hyperinsulinemia, insulin resistance (IR), increased risk of glucose intolerance, and type 2 diabetes. Family studies have indicated a genetic susceptibility to PCOS. The aims of this study were 1) to assess glucose tolerance status, gonadotropins, and androgens in first degree relatives of patients with PCOS; and 2) to assess IR in normal glucose tolerant (NGT) family members. One hundred two family members of 52 patients with PCOS [Mothers(PCOS) (n = 34; me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
117
2
15

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(152 citation statements)
references
References 28 publications
16
117
2
15
Order By: Relevance
“…A large study by Legro et al [13] confirmed that fasting insulin levels were elevated in 307 sisters of PCOS women, compared with 47 control participants. Two other studies [20,22] have also found that sisters and brothers of women with PCOS have significantly higher insulin levels (fasting or during OGTT) and homeostasis model assessment insulin resistance compared with control individuals. Finally, a recent study demonstrated that sisters of PCOS women have increased prevalence of the metabolic syndrome [24].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A large study by Legro et al [13] confirmed that fasting insulin levels were elevated in 307 sisters of PCOS women, compared with 47 control participants. Two other studies [20,22] have also found that sisters and brothers of women with PCOS have significantly higher insulin levels (fasting or during OGTT) and homeostasis model assessment insulin resistance compared with control individuals. Finally, a recent study demonstrated that sisters of PCOS women have increased prevalence of the metabolic syndrome [24].…”
Section: Discussionmentioning
confidence: 87%
“…To the best of our knowledge, nine studies have previously assessed the metabolic phenotypes of relatives of women with PCOS [13,[19][20][21][22][23][24][25]39]. The first of these studies concluded that glucose-stimulated hyperinsulinaemia was frequent in sisters (n=24) and brothers (n=5) of PCOS probands [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance increases with increasing body mass index (BMI) and waist circumference as a clinical sign of central obesity (7). Whilst a family history of obesity, insulin resistance, and T2DM appears to be more prevalent in affected women (8), it is unclear whether this association is due to environmental or inherited factors, thus implicating a genetic background. Several T2DM candidate genes, including those for insulin, the insulin receptor, and insulin receptor substrates, have been investigated in this context, indicating evidence for a genetic contribution to PCOS susceptibility (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…PCOS is characterized by the presence of hyperandrogenism, menstrual irregularities and, in a significant portion of patients, insulin resistance (2)(3)(4). The familial aggregation of PCOS, hyperandrogenism and associated metabolic abnormalities indicates a genetic origin for PCOS (5). Heterogeneous clinical manifestations influenced by ethnic factors indicate the involvement of environmental factors (6).…”
Section: Introductionmentioning
confidence: 99%